2014
DOI: 10.1155/2014/430629
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antiviral Susceptibility of Human and Avian Influenza Viruses over the Last Decade

Abstract: Antivirals play an important role in the prevention and treatment of influenza infections, particularly in high-risk or severely ill patients. Two classes of influenza antivirals have been available in many countries over the last decade (2004–2013), the adamantanes and the neuraminidase inhibitors (NAIs). During this period, widespread adamantane resistance has developed in circulating influenza viruses rendering these drugs useless, resulting in the reliance on the most widely available NAI, oseltamivir. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 79 publications
0
31
0
1
Order By: Relevance
“…Such a decomposition allows linking thermodynamic profiles from ITC with structural causes and, thus, is very helpful for guiding decision making in lead optimization. As an example, we found that compound 8 is optimal with respect to Amt (1), rimantadine (2), and compound 7 in terms of its configurational entropy contribution to binding; however, it is unsatisfactory in terms of its van der Waals energies with respect to 7. We therefore predicted profiles for compounds with smaller ring moieties, i.e., cyclopropyl or cyclobutyl substituents, at position 2 of the adamantane core.…”
Section: Design Of Inhibitors Based On Mm-pbsa Predictionsmentioning
confidence: 91%
“…Such a decomposition allows linking thermodynamic profiles from ITC with structural causes and, thus, is very helpful for guiding decision making in lead optimization. As an example, we found that compound 8 is optimal with respect to Amt (1), rimantadine (2), and compound 7 in terms of its configurational entropy contribution to binding; however, it is unsatisfactory in terms of its van der Waals energies with respect to 7. We therefore predicted profiles for compounds with smaller ring moieties, i.e., cyclopropyl or cyclobutyl substituents, at position 2 of the adamantane core.…”
Section: Design Of Inhibitors Based On Mm-pbsa Predictionsmentioning
confidence: 91%
“…123,124 Currently, circulating influenza A strains are susceptible to the neuraminidase inhibitors, including A(H5N1). 125 However, because circulating strains of A(H1N1) in 2008 exhibited resistance, one must be concerned that in the future, circulating influenza strains may develop resistance to neuraminidase inhibitors. Vaccines are available for A(H5N1) but not for A(H7N9).…”
Section: Infection Controlmentioning
confidence: 99%
“…The M2 inhibitor, amantadine (Symmetrel®) is effective only for influenza A. However, the dug is rarely used in Japan in recent years because of the universal resistance among influenza A(H1N1)pdm09 and A(H3N2) attributed to an amino acid mutation serine to asparagine at position 31 in the M2 protein [3942]. Thus, NAIs, which are effective against both influenza A and B, are now the drugs of choice for clinicians [3, 41] A newly developed RNA polymerase inhibitor, favipiravir (Avigan®), was approved in Japan in 2014, but the use is highly restricted due to its potential adverse effects [7, 9, 43].…”
Section: National Influenza Surveillancementioning
confidence: 99%